The Effect Of The Implementation Of Puerperium Intensive Care On Exclusive Breastfeeding - Windarti, Yunik; Amalia, Rizki (STRADA : Jurnal Ilmiah Kesehatan, 2020)
Exclusive breastfeeding is one of programs that grabs attention, where it is known that its achievements have never been successful according to the target that has been announced by the Indonesian government. Intensive care it is hoped that it will encourage mothers to provide exclusive breastfeeding. The aim to analyze effect of puerperium intensive care on the achievement of exclusive breastfeeding. Quasi experimental design, nonequivalent control group. Independent variables puerperium intensive care, dependent variable exclusive breastfeeding. Population of post-partum mothers using incidental sampling for 6 months in Wonokromo, instrument a questionnaire. Analyzed using chi-square test. Of the 31 respondents who received puerperium intensive care, most (58.06%) gave exclusive breastfeeding, of the 31 respondents who did not receive puerperium intensive care, most (67.74%) did not provide exclusive breastfeeding. The p value = 0.041 <α = 0.05 means there is an effect of puerperium intensive care on the achievement of exclusive breastfeeding